Pengaruh Variasi Latihan Push- Up terhadap Kemampuan Pukulan Smash Anggota UKM Pickleball Universitas Jambi - Miftahurrahman; Nugraha, Ugi; Mardian, Roli (MAN Insan Cendekia Jambi, 2025)
This study aims to examine the effect of push-up training variations on smash shot ability among members of the Pickleball Student Activity Unit (UKM) at Jambi University. The smash shot is a critical element in pickleball, requiring significant upper-body muscle strength and precision. Push-up exercises were selected due to their simplicity, equipment-free nature, and effectiveness in strengthening muscles involved in smash techniques. The research employed an experimental method with a one-group pre-test and post-test design, involving 11 active members of the Pickleball UKM at Jambi University as samples. Data were collected through smash shot ability tests before and after the push-up training intervention, which consisted of 18 sessions over one month. The results indicated a significant improvement in smash shot performance post-intervention, with mean scores increasing from 7.27 (pre-test) to 23.00 (post-test). A paired t-test revealed a significance level of <0.001, confirming the acceptance of the alternative hypothesis (Ha). Thus, it is concluded that push-up training variations significantly enhance smash shot ability in Pickleball UKM members at Jambi University.